Pole piece and preparation method thereof, battery and power utilization system

By designing specific first and second pore distributions in the active material layer of the lithium battery electrode sheet, the problems of insufficient wettability of the electrolyte and low ion mobility are solved, and the battery performance is improved, including power performance, fast charging performance and low temperature performance.

CN119833537APending Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311438729.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The infiltration performance of the electrolyte in lithium batteries is insufficient, resulting in low ion mobility, affecting the charging and discharging rate and energy efficiency of the battery, and thus shortening the service life of the battery.

Method used

An electrode sheet is designed, and its active material layer has a specific first pore and a second pore distribution. The pore size of the first pore is within the range of 0.05*D50≤R1<0.65*D50, and the pore size of the second pore is within the range of 0.65*D50≤R1≤10*D50. This pore distribution structure improves the wetting property and ion mobility of the electrolyte.

Benefits of technology

By optimizing the pore distribution structure of the electrode sheet, the wetting ability of the electrolyte in the active material is improved, the migration path of ions inside the electrode sheet is optimized, the overall internal resistance of the battery is reduced, and the power performance, fast charging performance and low-temperature performance of the electrode sheet is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833537A_ABST
    Figure CN119833537A_ABST
Patent Text Reader

Abstract

The invention discloses a pole piece and a preparation method thereof, a battery and a power utilization system. The pole piece comprises a current collector and an active material layer which are arranged in a laminated manner, the active material layer comprises a plurality of active particles, and the active material layer is further provided with first pores and second pores; the aperture R1 of the first pores and the aperture R2 of the second pores meet the following conditions: 0.05 * D50 < = R1 < 0.65 * D50, 0.65 * D50 < = R1 < = 10 * D50, D50 is the median particle size of the plurality of active particles, and the unit of R1 and R2 is nm. Through the pore distribution structure with matched size, the wettability of the electrolyte in the active material is improved, so that the migration path of ions in the pole piece is optimized, the overall internal resistance of the battery is reduced, and the power performance, the fast charging performance and the low-temperature performance of the pole piece are further improved on the basis of improving the ion mobility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a pole piece and a preparation method thereof, a battery and a power system. Background Art

[0002] In secondary batteries (taking lithium batteries as an example), the wetting properties of the electrolyte have a crucial impact on the battery performance. If the electrolyte does not wet the positive and negative electrodes of the battery well, it will affect the transmission of ions and the conduction of electrons, which will lead to a decrease in the ion mobility of the battery. When the electrolyte has poor wetting properties, the ion transmission rate inside the battery will be greatly reduced. This will not only affect the charge and discharge rate of the battery, but will also cause the battery to produce a large internal resistance during the charge and discharge process, reducing the energy efficiency of the battery. In addition, if the wetting properties of the electrolyte are insufficient, it may also cause the battery to have capacity attenuation, electrode material corrosion and other problems during the charge and discharge process. The emergence of these problems will further shorten the service life of the battery, so how to improve the wetting properties of the electrolyte to improve the performance of secondary batteries has become the key. Summary of the invention

[0003] The purpose of the present application is to provide a pole piece and a method for preparing the pole piece, a battery and a power system to solve the problems of poor electrolyte wettability and low ion mobility.

[0004] To achieve the purpose of this application, this application provides the following technical solutions:

[0005] In a first aspect, the present application provides a pole piece, comprising a current collector and an active material layer arranged in a stacked manner; the active material layer comprises a plurality of active particles, and the active material layer also has a first pore and a second pore; the pore size R1 of the first pore and the pore size R2 of the second pore satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R1≤10*D50, wherein D50 is the median particle size of the plurality of active particles, and the units of R1 and R2 are nm.

[0006] In one embodiment, the porosity A1 of the first pores satisfies: 15%≤A1≤34.5%; the porosity A2 of the second pores satisfies: 0.3%≤A2≤10%.

[0007] In one embodiment, the total porosity in the active material layer is σ, the total porosity σ includes the porosity A1 of the first pores and the porosity A2 of the second pores, and the total porosity σ satisfies: 25%≤σ≤35%, and A1+A2≤σ.

[0008] In one embodiment, the ratio η of the second pore to the first pore is A2 / A1, satisfying: 1%*(σ / A)≤η≤15%*(σ / A), wherein A is a correction coefficient for the total porosity of the active material layer, and A satisfies: 25%≤A≤35%.

[0009] In one embodiment, a ratio η of the second pore to the first pore is A2 / A1, satisfying: 1%*(σ / 30%)≤η≤15%*(σ / 30%).

[0010] In one embodiment, a ratio η of the second pore to the first pore is A2 / A1, satisfying: 1%≤η≤15%.

[0011] In one embodiment, the active material layer includes a first surface and a second surface opposite to each other, and the first surface is connected to the current collector; along the direction from the first surface to the second surface, the proportion of the second pores tends to first decrease and then increase.

[0012] In one embodiment, the median particle size D50 of the active particles satisfies: 100 nm ≤ D50 ≤ 30 μm.

[0013] In a second aspect, the present application provides a method for manufacturing an electrode, comprising: preparing a mixed powder containing active materials; preparing an active material layer using the mixed powder, and disposing the active material layer on a current collector; the active material layer comprises a plurality of active particles, and the active material layer also has a first pore and a second pore; the pore size R1 of the first pore and the pore size R2 of the second pore satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R1≤10*D50, wherein D50 is the median particle size of the active particles.

[0014] In one embodiment, preparing the mixed powder includes: premixing the active material, the binder and the conductive agent in proportion to obtain a premixed powder; and putting the premixed powder into a jet mill for grinding and mixing to obtain a jet mill mixed powder.

[0015] In one embodiment, the active material layer is prepared using the mixed powder and the active material layer is disposed on the current collector, including: rolling the air flow milled mixed powder to form a first self-supporting film sheet; rolling the first self-supporting film sheet to form a second self-supporting film sheet; and bonding the second self-supporting film sheet to the current collector to obtain the pole piece.

[0016] In a third aspect, the present application provides a battery, comprising a diaphragm and pole pieces as described in the above embodiment, wherein the pole pieces comprise a positive pole piece and a negative pole piece, and the positive pole piece and the negative pole piece are respectively arranged on opposite sides of the diaphragm.

[0017] In a fourth aspect, the present application provides an electricity consumption system, which includes an electric device and a battery as described in the above embodiment, and the battery is used to supply power to the electric device.

[0018] In the present application, the active material layer in the electrode has a first pore and a second pore, and the pore sizes of the first pore and the second pore meet a specific range. The larger second pore becomes a large high-speed channel with high-flux ion migration, and the smaller first pore becomes a dense capillary channel. The pore distribution structure with matched sizes is used to improve the wettability of the electrolyte in the active material, thereby optimizing the migration path of ions inside the electrode, reducing the overall internal resistance of the battery, and further improving the power performance, fast charging performance and low-temperature performance of the electrode on the basis of improving the ion mobility. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 is a schematic longitudinal cross-sectional view of a pole piece according to an embodiment;

[0021] Figure 2 is a schematic cross-sectional view of a pole piece according to an embodiment;

[0022] Figure 3 is a schematic longitudinal cross-sectional view of an active material layer according to an embodiment;

[0023] Figure 4 is a flow chart of a method for preparing a pole piece according to an embodiment;

[0024] Figure 5 It is the pore distribution diagram of Example 1 and Comparative Example 1.

[0025] Description of reference numerals:

[0026] 100 - pole piece, 10 - active material layer, 11 - first pore, 12 - second pore, 13 - active particles, 10A - first surface layer, 10B - second surface layer, 10C - middle layer, 101 - first surface, 102 - second surface, 20 - current collector. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0029] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0030] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0031] This application provides a pole piece 100, please refer to Figure 1 , including a current collector 20 and an active material layer 10 arranged in stacked layers; the active material layer 10 includes a plurality of active particles 13, and the active material layer 10 also has a first pore 11 and a second pore 12; the pore size R1 of the first pore 11 and the pore size R2 of the second pore 12 satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R1≤10*D50, wherein D50 is the median particle size of the plurality of active particles 13, and the units of R1 and R2 are nm.

[0032] Specifically, the electrode sheet 100 may be a positive electrode sheet or a negative electrode sheet. The electrode active material in the positive electrode sheet is the positive electrode active particles, and the electrode active material in the negative electrode sheet is the negative electrode active particles.

[0033] Optionally, the current collector 20 may be a foam metal mesh, a metal film material, etc., specifically including any one of copper foil and aluminum foil.

[0034] Optionally, when the electrode 100 is a positive electrode, the types of positive electrode active particles include lithium-embedded active particles, sodium-embedded active particles, potassium-embedded active particles, magnesium-embedded active particles, zinc-embedded active particles, and aluminum-embedded active particles. Taking lithium secondary batteries as an example, the positive electrode active particles are selected from LiCoO 2、LiNiO 2 、LiCo x Ni 1-x O 2 (0≤x≤1), LiCo x Ni 1-x-y Al y O 2 (0≤x≤1, 0≤y≤1), LiMn 2 O 4 、LiFe x Mn y M z O 4 (M is at least one of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn or Mo, 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), Li 1+x L 1-y-z M y N z O 2 (L, M, N are at least one of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S, B, -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1), LiFePO 4 , Li 3 V 2 (PO 4 ) 3 , Li 3 V 3 (PO 4 ) 3 、LiVPO 4 F. Li 2 CuO 2 , Li 5 FeO 4 , and metal sulfides and oxides such as TiS 2 、V 2 S 3 ,FeS,FeS 2 、LiMS x (M is at least one transition metal element such as Ti, Fe, Ni, Cu, Mo, etc., 1≤x≤2.5), TiO 2 Cr 3 O 8 、V 2 O 5 、MnO 2 At least one of the group consisting of etc.

[0035] Optionally, when the electrode sheet 100 is a negative electrode sheet, the negative electrode may include one or more of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode and an aluminum negative electrode. Among them, the carbon-based negative electrode may include graphite, hard carbon, soft carbon, etc.; the silicon-based negative electrode may include silicon, silicon carbon, silicon oxygen, silicon metal compounds, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy and a lithium indium alloy.

[0036] Optionally, when the pole piece 100 is a negative pole piece, the negative electrode active particles include one or more of natural graphite, artificial graphite, hard carbon, soft carbon, lithium titanate, iron oxide, lithium titanium phosphate, titanium dioxide, silicon, silicon oxide, aluminum, tin and antimony.

[0037] Optionally, the active material layer 10 also includes an adhesive, which includes one or more of tetrafluoroethylene and its copolymers, polyvinylidene fluoride and its copolymers, polyolefins and their copolymers, polyethers and their copolymers, polyphenylene ethers and their copolymers, polysiloxanes and their copolymers, polyesters and their copolymers, polyethylene oxide, polyethylene-polyethylene glycol block copolymers, polydimethylsiloxane, poly(dimethylsiloxane-co-alkylmethylsiloxane), nitrile rubber, polyvinyl ester, polyvinyl acetate, and polyacrylate.

[0038] Optionally, the polyolefin includes one or more of polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / vinylidene fluoride copolymer, and propylene / vinylidene fluoride copolymer; polytetrafluoroethylene and its copolymers can be one or more of tetrafluoroethylene / ethylene copolymer, tetrafluoroethylene / propylene copolymer, tetrafluoroethylene / vinylidene fluoride copolymer, tetrafluoroethylene / ether copolymer, tetrafluoroethylene / silicone copolymer, tetrafluoroethylene / branched polyether copolymer, tetrafluoroethylene / vinyl ether copolymer, and tetrafluoroethylene / branched polyether / vinyl ether copolymer.

[0039] Optionally, the active material layer 10 further includes a conductive agent, which may be one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fibers, graphene, and the like.

[0040] Optionally, the active material layer 10 may be a self-supporting film. The self-supporting film may be prepared by a dry electrode process, and the adhesive used is a polymer, and the polymer has a low bulk density. A polymer with a low bulk density is more likely to form a fluffy state, so that a self-supporting film with a suitable thickness can be obtained after a single hot pressing. The adhesive may be processed into a fibrous state by shear force, and the fibrous adhesive is mixed with the active particles 13 and prepared into a self-supporting film by hot pressing.

[0041] Furthermore, the active material layer 10 also has pores, including a first pore 11 and a second pore 12. The pore sizes of the first pore 11 and the second pore 12 are different, and the pore size of the second pore 12 is larger than that of the first pore 11. Figure 1 As shown, on the longitudinal section of the active material layer 10, the first pore 11 and the second pore 12 may have an irregular profile, and the apertures of the first pore 11 and the second pore 12 are the distances between the two closest points on their profiles; of course, the apertures of the first pore 11 and the second pore 12 may also be the distances between the two farthest points on their profiles. It is understandable that when the aperture of the first pore 11 is the distance between the two closest points on its profile, the second pore 12 should also adopt this measurement method.

[0042] The pore size R1 of the first pore 11 satisfies, 0.05*D50≤R1<0.65*D50; the pore size R2 of the second pore 12 satisfies, 0.65*D50≤R1≤10*D50. Wherein, D50 is the median particle size of the plurality of active particles 13, that is, the average particle size of the plurality of active particles 13. Therefore, in different pole pieces 100, the pore sizes of the first pore 11 and the second pore 12 depend on the particle size of the active particles 13 used.

[0043] The D50 can be obtained by testing the particle size cross-section of multiple active particles 13 on the longitudinal section of the active material layer 10 through a scanning electron microscope, and then measuring the particle size distribution using ImageJ software; on the longitudinal section of the active material layer 10, the active particles 13 have different contours, and the particle size of a single active particle 13 is obtained at the two nearest points of each particle contour.

[0044] The first pores 11 and the second pores 12 can be obtained by testing the pore size distribution curve of the pole piece.

[0045] Optionally, the pore size R1 of the first pore 11 may be, but is not limited to, 0.05*D50, 015*D50, 0.2*D50, 0.25*D50, 0.3*D50, 0.35*D50, 0.4*D50, 0.45*D50, 0.5*D50, 0.55*D50, 0.64*D50. The pore size R2 of the second pore 12 may be, but is not limited to, 0.65*D50, 1*D50, 2*D50, 3*D50, 4*D50, 5*D50, 6*D50, 7*D50, 8*D50, 9*D50, 10*D50. The units of R1 and R2 are nm.

[0046] It can be understood that the first pores 11 and the second pores 12 are channels in the active material layer 10 for electrolyte to penetrate and carry ions to flow. Figure 2As shown, in the cross section of the pole piece 100, the first pore 11 and the second pore 12 can be bent and extended in any direction ( Figure 2 In the case where the pore sizes of the first pore 11 and the second pore 12 are different, the flow rate of the electrolyte flowing through the first pore 11 is different from the flow rate of the electrolyte flowing through the second pore 12. Specifically, the flow rate of the electrolyte in the second pore 12 should be greater than the flow rate of the electrolyte in the first pore 11.

[0047] Optionally, in the unit volume of the active material layer 10, the first pores 11 and the second pores 12 are evenly distributed; that is, it can be understood that in the unit volume of the active material layer 10, the ratio of the proportion (porosity) of the first pores 11 to the proportion (porosity) of the second pores 12 satisfies a certain range. For example, in the unit volume of the active material layer 10, the porosity of the first pores 11 is A1, the porosity of the second pores 12 is A2, A2 / A1=η, and η is a constant value.

[0048] Therefore, in the active material layer 10, when the pore size of the first pore 11 is smaller than that of the second pore 12, the second pore 12 is a large high-speed channel with high-flux ion migration in the active material layer 10, and the first pore 11 is densely distributed in the active material layer 10 similar to capillary channels, thereby ensuring that ions penetrate between each active particle 13.

[0049] In the present application, the active material layer 10 in the electrode 100 has a first pore 11 and a second pore 12, and the pore sizes of the first pore 11 and the second pore 12 meet a specific range. The larger second pore 12 becomes a large high-speed channel with high-flux ion migration, and the smaller first pore 11 becomes a dense capillary channel. The pore distribution structure with matched sizes is used to improve the wettability of the electrolyte in the active material, thereby optimizing the migration path of ions inside the electrode 100, reducing the overall internal resistance of the battery, and further improving the power performance, fast charging performance and low temperature performance of the electrode 100 on the basis of improving the ion mobility.

[0050] In one embodiment, the total porosity in the active material layer 10 is σ, the total porosity σ includes the porosity A1 of the first pores 11 and the porosity A2 of the second pores 12, and the total porosity σ satisfies: 25%≤σ≤35%, and A1+A2≤σ.

[0051] Specifically, the total pores in the active material layer 10 are the spaces in the active material layer 10 that meet the requirements of electrolyte immersion and ion migration after the electrode sheet 100 is manufactured. The total porosity in the active material layer 10 is related to the particle size distribution of the active particles 13. When the particle size distribution of the active particles 13 is wider, the tap density and compaction density of the active material layer 10 are higher, resulting in a smaller total porosity in the active material layer 10; conversely, when the particle size distribution of the active particles 13 is narrower, the tap density and compaction density of the active material layer 10 are lower, resulting in a larger total porosity in the active material layer 10.

[0052] Optionally, the active material layer 10 may further include a third pore, and the pore size of the third pore may be smaller than the first pore 11. Therefore, it can be understood that the total porosity in the active material layer 10 is the sum of the porosity A1 of the first pore 11 and the porosity A2 of the second pore 12 (when there is a third pore, the porosity of the third pore is also included).

[0053] Optionally, σ may be, but is not limited to, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%.

[0054] By setting the total porosity in the active material layer 10 within the above range, the contact between the active particles 13 and the electrolyte can be improved, thereby increasing the utilization rate of the active material; and the appropriate porosity structure can provide the battery with appropriate mechanical strength and thermal stability, thereby increasing the service life and safety of the battery.

[0055] In one embodiment, the porosity A1 of the first pores 11 satisfies: 15%≤A1≤34.5%; and the porosity A2 of the second pores 12 satisfies: 0.3%≤A2≤10%.

[0056] Specifically, on the basis of the total porosity provided in the above embodiment, the porosity A1 of the first pore 11 and the porosity A2 of the second pore 12 are further provided, so that the porosity A1 of the first pore 11 is greater than the porosity A2 of the second pore 12. The advantage of this arrangement is that the first pore 11 has a larger proportion, thereby ensuring that ions penetrate into the capillary channels between the active particles 13 and exchange ions with the active particles 13.

[0057] Optionally, the porosity A1 of the first pore 11 may be, but is not limited to, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 34.5%.

[0058] Optionally, the porosity A2 of the second pores 12 may be, but is not limited to, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0059] In one embodiment, the ratio η of the second pores 12 to the first pores 11 is A2 / A1, satisfying: 1%*(σ / A)≤η≤15%*(σ / A), wherein A is a correction coefficient for the total porosity of the active material layer 10, and A satisfies: 25%≤A≤35%.

[0060] Specifically, in the above relationship, A is the correction coefficient of the total porosity in the active material layer 10, that is, the coefficient used to correct the total porosity σ based on the method for preparing the electrode 100 provided by the present application, so that the distribution reliability of the proportion of the porosity A1 of the first pore and the porosity A2 of the second pore is higher.

[0061] It is understandable that in actual production, the total porosity σ of each pole piece 100 is not a fixed value. Due to the error in the manufacturing process, the total porosity σ of each pole piece 100 should be within a range and can present a normal distribution, and A given in the present invention is the median of the total porosity σ of the pole piece 100. For example, the total porosity of the pole piece 100 needs to be 30%, but the actual total porosity σ of each pole piece 100 should be close to 30%, so a correction factor A of 30% can be added, and (σ / A) is the final correction factor close to 1, so that A2 / A1 in each pole piece 100 has high reliability.

[0062] Optionally, the correction factor A of the total porosity may be, but is not limited to, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%.

[0063] Since the active material layer 10 includes a plurality of active particles 13, the performance of the electrode 100 can be optimized by controlling the particle size distribution of the active particles 13 and the apertures of the first pores 11 and the second pores 12. For example, by controlling the range of the apertures R1 and R2, the porosity, air permeability, ion transfer rate of the active material layer 10 and the capacity, internal resistance and other performance parameters of the electrode can be adjusted. And through the above relationship, the aperture range of the two pores in the active material layer 10 can be further customized, and the aperture size can be adjusted according to the needs of a specific application to optimize the battery performance.

[0064] In one embodiment, the ratio η of the second pores 12 to the first pores 11 is A2 / A1, satisfying: 1%*(σ / 30%)≤η≤15%*(σ / 30%).

[0065] Specifically, the total porosity in the obtained active material layer 10 is about 30%. Therefore, when 30% is set as the correction coefficient A of the total porosity in the active material layer 10, the total porosity σ in the active material layer 10 is the actual measured total porosity of the manufactured pole piece 100, and the ratio of the two (σ / 30%) can be understood as the correction of the ratio η of the second pore 12 to the first pore 11.

[0066] In one embodiment, the ratio η of the second pores 12 to the first pores 11 is A2 / A1, satisfying: 1%≤η≤15%.

[0067] Optionally, when σ is equal to 30% and A is equal to 30%, the ratio η of the second pore 12 to the first pore 11 can be but is not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.

[0068] In one implementation, please refer to Figure 3 The active material layer 10 includes a first surface 101 and a second surface 102 facing each other, and the first surface 101 is connected to the current collector 20; along the direction from the first surface 101 to the second surface 102, the proportion of the second pores 12 decreases first and then increases.

[0069] Specifically, the pole piece 100 provided in the present application has a differentiated pore distribution structure in which the proportion of the second pores 12 on the surface layer closer to the active material layer 10 is higher.

[0070] like Figure 3 As shown, the active material layer 10 includes a first surface 101 and a second surface 102 opposite to each other. The active material layer 10 can be divided into a first surface layer 10A, a second surface layer 10B and an intermediate layer 10C ( Figure 3 The first surface layer 10A includes a first surface 101, and the second surface includes a second surface 102. In the first surface layer 10A (or the second surface layer 10B), the proportion of the second pores 12 may be greater than the proportion of the first pores 11; in the intermediate layer 10C, the proportion of the second pores 12 may be less than the proportion of the first pores 11. Furthermore, the proportion of the second pores 12 in the active material layer 10 may change regularly, that is, along the thickness direction of the active material layer 10, the proportion of the second pores 12 tends to decrease first and then increase. It should be explained that the proportion of the second pores 12 is the ratio of the second pores 12 to the total pores in the unit volume of the active material layer 10.

[0071] By setting the proportion of the second pores 12 in the active material layer 10 to first decrease and then increase, the second pores 12 at the surface layer account for a larger proportion, so that the electrolyte can more easily penetrate the active material layer 10 from the surface layer, thereby improving the wettability of the electrolyte; moreover, the first pores 11 in the middle layer 10C account for a larger proportion, which can improve the contact between the electrolyte and each active particle 13, and further improve the wettability of the electrolyte to the active material layer 10 as a whole.

[0072] In one embodiment, the median particle size D50 of the active particles 13 satisfies: 100 nm ≤ D50 ≤ 30 μm. Specifically, the median particle size D50 of the active particles 13 satisfies the above relationship, which can better control the particle size in the active material layer 10, avoid the particle size being too small or too small, and thus ensure that the active material can have the first pore 11 and the second pore 12.

[0073] Optionally, the median particle size D50 of the active particles 13 may be, but is not limited to, 100 nm, 200 nm, 300 nm, 500 nm, 800 nm, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, or 30 μm.

[0074] By controlling the lower and upper limits of the particle size of the active particles 13 and combining with the relationship in the above embodiment, the porosity and distribution ratio of the first pores 11 in the active material layer 10 can be reasonably set, thereby ensuring the requirements of electrolyte immersion and ion migration in the active material layer 10 while obtaining a high-capacity electrode 100.

[0075] In one embodiment, the present application also provides a method for manufacturing a pole piece, please refer to Figure 4 , including the following steps:

[0076] Step S10, preparing a mixed powder containing active materials.

[0077] Step S20, preparing an active material layer using the mixed powder, and disposing the active material layer on the current collector.

[0078] The active material layer includes a plurality of active particles, and the active material layer also has a first pore and a second pore; the pore size R1 of the first pore and the pore size R2 of the second pore satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R1≤10*D50, wherein D50 is the median particle size of the active particles.

[0079] Specifically, in step S10, preparing the mixed powder includes: premixing the active material, the binder and the conductive agent in proportion to obtain a premixed powder; and putting the premixed powder into a jet mill for grinding and mixing to obtain a jet mill mixed powder.

[0080] Optionally, weigh the active material (particles), binder, and conductive agent in corresponding proportions and put them into a V-type mixer for premixing. The amount of the binder is 1.5% to 5%, and the amount of the conductive agent is 0.3% to 2%. Then, the premixed mixed powder is put into a jet mill for grinding and mixing, and the crushing pressure range is 0.1MPa to 0.8MPa.

[0081] Optionally, in step S20, preparing an active material layer using a mixed powder may include: rolling the airflow milled mixed powder to form a first self-supporting film; rolling the first self-supporting film to form a second self-supporting film; and bonding the second self-supporting film to the current collector to obtain the pole piece.

[0082] Optionally, the obtained airflow mill mixed powder is rolled into a self-supporting membrane (i.e., the first self-supporting membrane) by a hot roller press. The rolling line pressure range is 0.1t / cm~1t / cm, the differential ratio is 1:1~1:3, and the temperature range is 100℃~250℃. Then, the self-supporting membrane is subjected to 2-stage calendering by a calendering roller press to obtain a thinned membrane (i.e., the second self-supporting membrane), with a calendering line pressure of 0.1t / cm~1t / cm, a differential ratio of 1:1~1:3, and a temperature range of 60℃~180℃. Finally, the two membranes are hot-pressed with a foil with a primer to form a pole piece with the required porosity. By controlling the calendering line pressure of 0.1t / cm~1t / cm and the differential ratio of 1:1~1:3, the self-supporting membrane can present a regular pore distribution.

[0083] Optionally, the proportion of the second pores in the active material layer (i.e., the self-supporting membrane) may change regularly, i.e., along the thickness direction of the active material layer, the proportion of the second pores decreases first and then increases. It should be explained that the proportion of the second pores is the ratio of the second pores to the total pores in the unit volume of the active material layer.

[0084] Optionally, the active material (particles), binder, and conductive agent in this embodiment can all refer to those provided in the above embodiments, and will not be described in detail here.

[0085] In one embodiment, the present application further provides a battery, comprising a diaphragm and the above-mentioned electrode sheet, wherein the electrode sheet comprises a positive electrode sheet and a negative electrode sheet, and the positive electrode sheet and the negative electrode sheet are respectively arranged on opposite sides of the diaphragm. The present application does not limit the specific type of battery, and both the positive electrode sheet and the negative electrode sheet of the battery can be prepared using the above method.

[0086] In one embodiment, the present application further provides an electric system, the electric system comprising electric equipment and a battery, the battery being used to supply power to the electric equipment. The electric system may be a new energy vehicle or an energy storage power station.

[0087] The technical solution of the present invention is described in detail below through specific embodiments.

[0088] Example 1

[0089] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 90 nm, and the porosity A1 of the first pore is 26.7%; the second pore is about 1 μm, and the porosity A2 of the second pore is 4%, and the correction coefficient A is 30%. The manufacturing method of the positive electrode sheet is as follows:

[0090] 1) Lithium iron phosphate, conductive agent and binder were added into a V-type mixer in a ratio of 100:1:3 and mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0091] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:1, and a temperature of 150°C.

[0092] 3) The initially formed electrode is rolled to 220 g / m by a rolling roller with a pressure of 1 t / cm, a differential speed of 1:1, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0093] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0094] Example 2

[0095] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 200 nm, and the porosity A1 of the first pore is 28%; the second pore is about 700 nm, and the porosity A2 of the second pore is 2%, and the correction coefficient A is 30%. The manufacturing method of the positive electrode sheet is as follows:

[0096] 1) Lithium iron phosphate, conductive agent and binder are added into a V-type mixer in a ratio of 100:1:3, mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0097] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:1.5, and a temperature of 150°C.

[0098] 3) The initially formed electrode is rolled to 220g / m by a rolling roller with a pressure of 1t / cm, a differential speed of 1:1.5, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0099] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0100] Example 3

[0101] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 90 nm, and the porosity A1 of the first pore is 23.5%; the second pore is about 1 μm, and the porosity A2 of the second pore is 2.5%, and the correction coefficient A is 25%. The manufacturing method of the positive electrode sheet is as follows:

[0102] 1) Lithium iron phosphate, conductive agent and binder were added into a V-type mixer in a ratio of 100:1:3 and mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0103] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:1, and a temperature of 150°C.

[0104] 3) The initially formed electrode is rolled to 220 g / m by a rolling roller with a pressure of 1 t / cm, a differential speed of 1:1, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0105] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0106] Example 4

[0107] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 600 nm, and the porosity A1 of the first pore is 34%; the second pore is about 9000 nm; the porosity A2 of the second pore is 0.4%, and the correction coefficient A is 35%. The manufacturing method of the positive electrode sheet is as follows:

[0108] 1) Lithium iron phosphate, conductive agent and binder are added into a V-type mixer in a ratio of 100:1:3, mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0109] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:2, and a temperature of 150°C.

[0110] 3) The initially formed electrode is rolled to 220 g / m by a rolling roller with a pressure of 1 t / cm, a differential speed of 1:3, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0111] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0112] Example 5

[0113] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 500 nm, and the porosity A1 of the first pore is 35%; the second pore is about 8800 nm; the porosity A2 of the second pore is 0.4%, and the correction coefficient A is 35%. The manufacturing method of the positive electrode sheet is as follows:

[0114] 1) Lithium iron phosphate, conductive agent and binder are added into a V-type mixer in a ratio of 100:1:3, mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0115] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:2.5, and a temperature of 150°C.

[0116] 3) The initially formed electrode is rolled to 220 g / m by a rolling roller with a pressure of 1 t / cm, a differential speed of 1:3, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0117] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0118] Example 6

[0119] This embodiment provides a positive electrode sheet, the active particles are lithium iron phosphate, the active material layer has a first pore and a second pore, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 550 nm, and the porosity A1 of the first pore is 38%; the second pore is about 8000 nm; the porosity A2 of the second pore is 0.2%, and the correction coefficient A is 40%. The manufacturing method of the positive electrode sheet is as follows:

[0120] 1) Lithium iron phosphate, conductive agent and binder are added into a V-type mixer in a ratio of 100:1:3, mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0121] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a differential speed of 1:3, and a temperature of 150°C.

[0122] 3) The initially formed electrode is rolled to 220 g / m by a rolling roller with a pressure of 1 t / cm, a differential speed of 1:3, and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0123] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0124] Comparative Example 1

[0125] Conventional wet coating was used. The ratio of lithium iron phosphate, conductive agent and binder was 100:1:3. They were added into a mixer to prepare wet slurry, which was then coated onto aluminum foil. The surface density was controlled to be 220g / m 2 , and then the compaction was controlled by roller pressing to 2.5g / cm 3 ; The obtained positive electrode plate has active particles of lithium iron phosphate, and the active material layer has first pores and second pores, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is about 800 nm, and the porosity A1 of the first pore is 28%; wherein the second pore is about 11 μm, and the porosity A2 of the second pore is 0.015%, and the correction coefficient A is 28%.

[0126] Comparative Example 2

[0127] This embodiment provides a positive electrode plate. The obtained positive electrode plate has active particles of lithium iron phosphate, and has first pores and second pores in the active material layer, wherein the particle size D50 of the active particles is 1 μm; wherein the first pore is approximately 40 nm, and the porosity A1 of the first pore is 25%; wherein the second pore is approximately 1 μm, and the porosity A2 of the second pore is 0.12%, and the correction coefficient A is 25%.

[0128] The method of making the positive electrode is as follows:

[0129] 1) Lithium iron phosphate, conductive agent and binder are added into a V-type mixer in a ratio of 100:1:3, mixed, and then put into a jet mill and ground at a pressure of 0.6 MPa to obtain a homogenized dry powder.

[0130] 2) The homogenized dry powder was uniformly conveyed to a horizontal hot roller press with a pressure of 1 t / cm, a roller gap of 100 μm, a uniform roller speed, and a temperature of 150°C.

[0131] 3) The initially formed electrode is rolled to 220g / m by a rolling roller at a pressure of 1t / cm, a uniform speed and a temperature of 150°C. 2 Surface density (the calendering roll gap is adjusted according to the surface density).

[0132] 4) The rolled electrode and the aluminum foil with the primer layer are thermally compounded at 150°C to obtain the target electrode, and then the electrode is compacted to 2.5g / cm by roller pressing. 3 .

[0133] The pole pieces provided in the above Examples 1 to 6 and Comparative Examples 1 to 2 are subjected to the following calculations and tests:

[0134] The ratio of the second pore to the first pore is η = A2 / A1, and the compacted density is 2.5 g / cm 3 The overall porosity σ of the corresponding lithium iron phosphate is 30%.

[0135] Porosity and pore distribution test (using mercury intrusion method): test range 0.1psia~61000psia.

[0136] Aperture test method: Use scanning electron microscope to test, and then use ImageJ software to measure the distance distribution between the two nearest points of the contour.

[0137] Pole piece DCIR (direct current internal resistance) test: ensure the counter electrode is consistent, you can use lithium sheet as the counter electrode, adjust the discharge to 50% SOC after formation, let it stand for 1 hour, and then discharge at 1.5C for 30s. The difference between the end voltage and the starting voltage is ΔV, and the test current of 1.5C is I, then DCIR = ΔV / I.

[0138] Rate performance test: The battery is prepared as above. After being divided into different capacities, it is charged to 100% SOC at 0.33C, and then discharged to the cut-off voltage at 1C and 3C to obtain different rate capacities. The 3C rate capacity is divided by the 1C rate capacity to obtain the rate capacity percentage Q.

[0139] Low temperature performance test: The battery was prepared as above. After being divided into different capacities, it was charged to 100% SOC at 0.33C. Then it was discharged to the cut-off voltage at 0.33C at 25℃ and 0℃ respectively to obtain different low temperature capacities. The capacity at 0℃ was divided by the capacity at 25℃ to obtain the low temperature capacity percentage q.

[0140] After testing and calculation, the performance comparison results in Table 1 were obtained.

[0141] Table 1

[0142]

[0143] Figure 5 1 is a pore distribution diagram of Example 1 and Comparative Example 1, wherein the new pore distribution is Example 1 and the traditional pore distribution is Comparative Example 1. Figure 5 It can be seen that the distribution rate of macropores in Example 1 is higher than that in Comparative Example 1, which also illustrates that the electrode prepared according to the manufacturing method provided in the present application has pore distribution with different pore sizes.

[0144] From the test results in Table 1, it can be seen that the ratio of the second pore to the first pore in Examples 1 to 6 is greater than that in Comparative Examples 1 and 2, which also shows that the proportion of large pores in the examples is relatively large. Therefore, under the effect of large pores and small pores, the DC internal resistance DCIR, rate capacity percentage Q, and low temperature capacity percentage q of the electrode are higher than those in Comparative Examples 1 and 2. This shows that the synergistic effect of the first pore and the second pore can improve the performance of the battery.

[0145] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0146] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A pole piece, characterized in that: include: Current collectors and active material layers stacked in layers; The active material layer includes a plurality of active particles, and the active material layer also has a first pore and a second pore; The pore size R1 of the first pore and the pore size R2 of the second pore satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R2≤10*D50, wherein D50 is the median particle size of the plurality of active particles, and the units of R1 and R2 are nm.

2. The pole piece according to claim 1, characterized in that: The porosity A1 of the first pores satisfies: 15%≤A1≤34.5%; the porosity A2 of the second pores satisfies: 0.3%≤A2≤10%.

3. The pole piece according to claim 2, characterized in that: The total porosity in the active material layer is σ, the total porosity σ includes the porosity A1 of the first pores and the porosity A2 of the second pores, and the total porosity σ satisfies: 25%≤σ≤35%, and A1+A2≤σ.

4. The pole piece according to claim 3, characterized in that: The ratio η of the second pore to the first pore is A2 / A1, satisfying: 1%*(σ / A)≤η≤15%*(σ / A), wherein A is a correction coefficient of the total porosity of the active material layer, and A satisfies: 25%≤A≤35%.

5. The pole piece according to claim 4, characterized in that: A ratio η of the second pore to the first pore is A2 / A1, which satisfies: 1%*(σ / 30%)≤η≤15%*(σ / 30%).

6. The pole piece according to claim 2, characterized in that: The ratio η of the second pore to the first pore is A2 / A1, which satisfies: 1%≤η≤15%.

7. The pole piece according to claim 1, characterized in that: The active material layer includes a first surface and a second surface opposite to each other, the first surface is connected to the current collector; along the direction from the first surface to the second surface, the proportion of the second pores shows a trend of first decreasing and then increasing.

8. The pole piece according to any one of claims 1 to 7, characterized in that: The median particle size D50 of the active particles satisfies: 100 nm ≤ D50 ≤ 30 μm.

9. A method for manufacturing a pole piece, characterized in that: include: preparing a mixed powder comprising active materials; Using the mixed powder to prepare an active material layer, and placing the active material layer on a current collector; The active material layer includes a plurality of active particles, and the active material layer also has a first pore and a second pore; The pore size R1 of the first pore and the pore size R2 of the second pore satisfy: 0.05*D50≤R1<0.65*D50, 0.65*D50≤R1≤10*D50, wherein D50 is the median particle size of the active particles.

10. The production method according to any one of claim 9, characterized in that: The preparation of the mixed powder comprises: Premixing the active material, the binder and the conductive agent in proportion to obtain a premixed powder; The premixed powder is put into a jet mill for grinding and mixing to obtain jet mill mixed powder.

11. The production method according to any one of claim 10, characterized in that: The active material layer is prepared by using the mixed powder, and the active material layer is disposed on the current collector, comprising: The jet milled mixed powder is rolled to form a first self-supporting film; Calendering the first self-supporting film to form a second self-supporting film; The second self-supporting film is bonded to the current collector to obtain the pole piece.

12. A battery, characterized in that: It comprises a diaphragm and a pole piece as described in any one of claims 1 to 8, wherein the pole piece comprises a positive pole piece and / or a negative pole piece.

13. An electricity system, characterized in that: The power consumption system comprises a power consumption device and a battery as claimed in claim 12, wherein the battery is used to supply power to the power consumption device.

Citation Information

Cited By

  • Electrode sheet and preparation method therefor, and battery and electric system

    EP4800749A1

  • Electrode sheet and preparation method therefor, and battery and electric system

    WO2025092701A1